Actions for Teaching and Learning Facilitated in Botany in Schools - Alves Nunes Faria, Jaquelina; de Souza Peçanha, Raphael (Guará Journal, 2019)
The  botanical  theme  has  been  little  noticed  in schools,  among  the  reasons  are  terminologies  and teaching  methodologies,  usually  fo-cused  on  the textbook.  In  this  context,  herbarium  and  laboratories become efficient didactic instruments, enabling students to know a reality  that  they  are  not  inserted.  The objective  was  to  show  viable  alternatives to teach and to learn botany within Science / Biology in basic education,  reflecting  on  the  initial  formation  of students  and  placing them as active agents in the construction of knowledge. The target were students and teachers of the schools of Carangola and region. Different themes and methodologies were chosen for the as-sembly of the dynamic classes, in order to teach botany in a different way. 701 students from nine schools were received. The work provid-ed a better understanding of botanical content and awakened envi-ronmental awareness in students. In addition, it showed how much the HUEMG herbarium is important for the region and provided initi-ation to teaching to students graduating in Biology.
Keywords: Education; Botany; Herbarium; Introduction to Teaching; Environmental education